2011
DOI: 10.1136/jnnp-2011-300979
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal deep brain stimulation for DYT6 dystonia

Abstract: While early results of pallidal DBS for DYT6 dystonia are encouraging, further research and additional subjects are needed both to optimise stimulation parameters for this population and to elucidate more accurately their response to surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 30 publications
4
65
0
Order By: Relevance
“…These results mirror previously published experiences supporting the value of surgery for the treatment of SD and reflect the general efficacy of DBS as a treatment for primary dystonia [34,35,36,37,38]. In contrast to the immediate effects of DBS on essential tremor and Parkinson's disease, the clinical response to DBS for dystonia may not manifest for weeks to months [36,40,41].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results mirror previously published experiences supporting the value of surgery for the treatment of SD and reflect the general efficacy of DBS as a treatment for primary dystonia [34,35,36,37,38]. In contrast to the immediate effects of DBS on essential tremor and Parkinson's disease, the clinical response to DBS for dystonia may not manifest for weeks to months [36,40,41].…”
Section: Discussionsupporting
confidence: 85%
“…Over the past 15 years, DBS of the globus pallidus pars interna (GPi) has been used to treat dystonia in both children and adults with favorable short- and long-term results [31,32,33,34,35,36,37,38]. Coubes et al [23] first reported the successful use of pallidal DBS for the treatment of acute SD in 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed one of the three (with DYT11) showed an 81% improvement in BFM-S; the patients with DYT6 showed 23% and 52% improvements. The patient with DYT11 (myoclonus dystonia) also saw an improvement in myoclonic symptoms, although this was not quantified, The literature concerning the response to DBS in patients with mutations at loci other than DYT1 is sparse, however in the small numbers with DYT627 28 and DYT1129 that have been reported, the results have been encouraging. It is clear at least that individual cases with DYT6 or DYT11 mutations have the potential to respond as well to treatment as the typical patient with DYT1 does.…”
Section: Discussionmentioning
confidence: 96%
“…However, recent reports of GPi DBS in a small number of patients with DYT6 have shown less robust results than in DYT1 patients. Panov et al [8] reported that DYT6 patients initially responded to pallidal stimulation much like DYT1 patients, but seemed to regress after 1-2 years of stimulation. This was also observed for the patient described here.…”
Section: Discussionmentioning
confidence: 99%
“…While medical therapy for primary dystonia is largely unsatisfactory, deep brain stimulation (DBS) of the globus pallidus internus (GPi) is demonstrated to be a safe and effective intervention for a wide range of dystonia subtypes, including DYT6 dystonia [5,6]. However, recent reports have also shown that unlike other primary dystonias such as DYT1 dystonia, DYT6 dystonia is often treated unsatisfactorily with pallidal DBS [7,8,9]. Here, we report a striking benefit obtained with DBS of the thalamic ventral lateral anterior (VLa) nucleus in a patient with DYT6 dystonia whose symptoms were refractory to both pharmacotherapy and GPi DBS.…”
Section: Introductionmentioning
confidence: 99%